DEVELOPMENT OF MATHEMATICS MODULE BASED ON THE PROBLEM SOLVING STRATEGY TO MEASURE HIGH ORDER THINKING ABILITY OF STUDENTS - Ruth Mayasari Simanjuntak; Dame Ifa Sihombing (State Islamic University of North Sumatra, 2022)
Penelitian ini merupakan penelitian pengembangan yang bertujuan untuk mengetahui proses pengembangan bahan ajar matematika berbasis strategi problem solving pada pokok bahasan bilangan berpangkat dan bentuk akar kelas IX SMP. Jenis penelitian yang digunakan adalah penelitian Research & Development (R&D). Subjek penelitian adalah siswa kelas IX SMPN 3 Percut Sei Tuan. Berdasarkan hasil pengembangan modul diperoleh modul yang valid, praktis, efektif, dan dapat mengukur kemampuan tingkat tinggi peserta didik. (1) Valid, Hasil validasi dari para ahli menyatakan bahwa nilai rata-rata aspek modul barbasis strategi problem solving pada materi bilangan berpangkat dan bentuk akar adalah 3,57. (2) Praktis, berdasarkan hasil uji coba skala besar/ lapangan mendapat nilai N 73,380 dengan kriteria Praktis. (3) Efektif, hasil uji keefektifan yang dilakukan saat uji coba lapangan 17 peserta didik yang tuntas dan 7 peserta didik yang tidak tuntas dalam mengerjakan soal. Uji efektifitas peserta didik yang dilakukan diketahui bahwa presentasi ketuntasan mendapat hasil hingga 70,83 % dengan kriteria efektif. (4) Kemampuan berpikir tingkat tinggi pada sampel sebesar 61,17% dengan kriteria baik. Dari data tersebut menunjukkan bahan ajar pembelajaran layak digunakan berdasarkan respon pendidik dan keefektifan yang dilakukan oleh peserta didik maka pengembangan modul matematika layak digunakan di sekolah. Keunggulan modul ini adalah lebih efisien, efektif dan terjadi pemerataan pemahaman terhadap materi yang disampaikan.AbstractThis is development research that aims to determine the process of developing mathematics teaching materials based on problem-solving strategies on the subject of numbers with exponents and root forms for the ninth-grade students of junior high school. This study follows a Research & Development (R&D) research type. The research subjects were the ninth-grade students of SMPN 3 Percut Sei Tuan. Based on the results of the module development, a module that is valid, practical, effective, and can measure the high-level abilities of students is considered as follows. (1) Valid, the results of the validation from the experts stated that the average value of the aspect of the problem-solving strategy-based module on the matter of numbers with exponents and root forms was 3.57. (2) Practical, based on the results of large-scale/field trials, the score is N 73,380 with Practical criteria. (3) Effective, the results of the effectiveness test conducted during the field trial were 17 students who were successful and 7 students who were not successful in completing the questions. The effectiveness test was known based on the percentage of learning mastery up to 70.83% with effective criteria. (4) Higher order thinking ability in the sample is 61.17% with good criteria. Based on these data, it reveals that teaching and learning materials are suitable based on the response of educators and the effectiveness of the students. Thus, the development of the mathematics module is appropriate to be used at schools. The advantages of this module are that it is more efficient and effective and there is an equal understanding of the material presented.